Access to justice as a guarantee of economic, social, and cultural rights. A review of the standards adopted by the Inter-American System of Human Rights (IACHR [S.l.], 2007)
Highlights and systematizes the case law of the IASHR - both the IACHR and the Court - on four core issues that it has regarded as priorities for the judicial protection of economic, social and cultural rights.
Keywords: ADMINISTRATION OF JUSTICE